Soil Quality of the Land under Coffee-Based Farming System (Case Study at Sumberjaya, West Lampung) - AI DARIAH; F. AGUS; . MASWAR (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2005)
Forest conversion to coffee-based farming systems has raised concern among many stakeholders since it may create serious impact to the deterioration of forest functions, declining soil productivity in particular and land degradation in general. Study on the impact of forest conversion on changes of soil quality, and the role of coffee for soil quality recovery has been conducted at Bodong and Laksana Sub Village of Sumberjaya Village, West Lampung. In Laksana, the observed landuse consisted of young (< 3 years) coffee plantation, mature (> 10 years) coffee, mix farming (multistrata), caliandra and forest, while in Bodong are young and mature coffee plantations and forest. The soil quality parameters used in this experiment were soil organic matter status and soil physical properties. Changes of soil quality as affected by forest conversion to coffee farming depends on soil resistance (resilience to structural break down). Soils with low resistance are easier to degrade than those with high soil resistance. The mix (multistarata) system shows better impact on soil quality than monoculture system does.